EFFECTS OF DIETARY PYRIDOXINE LEVELS ON GROWTH AND VITAMIN B6 PROFILE OF JUVENILE KURUMA PRAWN, Penaeus japonicus - I Nyoman Adiasmara Giri (Research Center for Fisheries, 1997)
The effects of dietary pyridoxine levels (0, 5, 15. and 25mg/100g diet) on growth andvitamin 86 profile of' juvenile Penaeus japonicus (0.69 + 0.03g; mean + sd) wereinvestigated during 8 weeks of f'eeding experiments.